Enantioselective Synthesis of Cyclobutylboronates - Yuan, Fushan; Yan, Xufei; Xia, Ying (Synlett, 2024)
Cyclobutane derivatives are important motifs in natural products and bioactive compounds. Owing to their inherent strain, the asymmetric synthesis of cyclobutanes remains a formidable challenge. With the development of various stereospecific transformations of alkylboronic esters, chiral cyclobutylboronates are expected to serve as promising synthetic intermediates for accessing chiral cyclobutane derivatives. However, obtaining highly enantioenriched cyclobutylboronates poses a daunting task in the field of organic synthesis. In this context, we highlight recent significant advances in the synthesis of chiral cyclobutylboronates.1 Introduction2 Enantioselective Borylation of Cyclobutenes3 Enantioselective Borylation of Cyclobutanes4 Other Methods5 Conclusions
Keywords: cyclobutanes; cyclobutylboronates; asymmetric synthesis; borylation; strained rings